The Aspect of Symbolism In Bharatas Dramaturgy: Unveiling the Significance of Symbolism in Bharatas Dramaturgy (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Bharatis considered as the father of India stylised dramatorgy.  It is most important text on dramaturgy.  That ancient India ever produced.  The title in its simplest sense literallymeans.  ‘Drama Science’ that is thescience of Dramas.